Metode Pembinaan “Mios” Untuk Meningkatkan Pendidik Profesional Dalam Profesional Learning Generasi Usia Emas Di Smp Prakarya Santi Asromo Majalengka Provinsi Jawa Barat - Slam, Zaenul (Fajar: Media Komunikasi Dan Informasi Pengabdian Kepada Masyarakat, 2020)
This article examines the "MIOS" coaching method at Prakarya Santi Asromo Majalengka Middle School, West Java Province. The results of this community service show that: First, monitoring as an activity in the early stages of service treatment shows that the implementation of professional learning for the golden age generation has not run optimally. Second, the results of in-service by service providers in the form of workshops have an impact on increasing the professionalism of educators. Third, the implementation of on-service by servants in the form of classroom observations has an impact on increasing professional educators in the implementation of professional learning for the golden age generation. The increase in professional educators in the implementation of professional learning is seen in the improvement of the pedagogical competence of educators, especially in the implementation of learning. In addition, it also has an impact on improving the quality of the process and learning outcomes of students. Therefore, it is necessary to develop professional educators in the implementation of professional learning for the golden age generation with the MIOS coaching method. Keywords:  Professional Teacher, Professional Learning,  MIOS  Abstrak:Artikel ini mengkaji mengenai metode pembinaan  “MIOS” di  SMP Prakarya Santi Asromo Majalengka Provinsi Jawa Barat. Hasil pengabdian masyarakat ini menunjukkan bahwa: Pertama, monitoring  sebagai kegiatan tahap awal  treatment  pengabdi menunjukkan  bahwa implementasi professional learning untuk generasi usia emas belum berjalan dengan optimal. Kedua,  hasil in service oleh pengabdi  dalam bentuk workshop  memberikan dampak  terhadap peningkatan profesionalisme  pendidik.  Ketiga, Pelaksanaan on service  oleh pengabdi dalam bentuk observasi kelas berdampak pada peningkatan  pendidik profesional dalam implementasi  professional learning untuk generasi usia emas. Peningkatan pendidik profesional dalam implementasi professional learning tampak dalam  peningkatan kompetensi pedagogik pendidik terutama dalam pelaksanaan pembelajaran. Selain itu berdampak pula pada peningkatan mutu proses dan hasil pembelajaran peserta didik.  Oleh karena itu, maka diperlukan pembinaan pendidik professional dalam implementasi professional learning untuk generasi usia emas dengan metode  pembinaan  MIOS. Kata Kunci: Pendidik Profesional, Professional Learning, MIOS